Microbial players in autoimmunity: multicentric analysis of the association between Mycoplasma hominis serostatus and rheumatoid arthritis - G. L. Erre; Ngoc Dan Thanh Phan; N. Diaz; A. Congiargiu; N. Mundula; A. A. Mangoni; Thi Minh Phuong Phan; V. Margarita; P. L. Fiori; P. Rappelli; C. Cacciotto; A. Alberti; et al. (Microbiology Spectrum)
ABSTRACT Resident mucosal pathogens may induce immune tolerance breach, specific autoimmune response, and the development of rheumatoid arthritis (RA) in susceptible individuals. Despite a number of studies linking infections by Mollicutes bacteria to autoimmune disorders’ onset and progression, the role of Mycoplasma hominis, a common urogenital mucosa colonizing bacterium, in inducing a specific humoral response in RA has been seldom addressed. This study reports M. hominis seroprevalence in RA patients compared to healthy controls (HC) by testing two separate cohorts sampled in two distinct geographical settings (Italy and Vietnam). The amount of circulating anti-lipid-associated membrane proteins (LAMPs) antibodies was significantly higher in RA patients than HC in both cohorts. Also, a significantly higher seroprevalence of anti-M. hominis antibodies in RA patients compared to HC in both cohorts was observed. Notably, neither ELISA OD values nor positivity of anti-LAMPs were significantly associated with RA-specific variables. Further studies are essential to elucidate the underlying mechanisms by which Mycoplasma species may contribute to the pathogenesis of RA, thereby advancing our understanding of the potential causal links between Mollicutes and autoimmune disorders.IMPORTANCEMycoplasmas may cause persistent asymptomatic mucosal infections and elicit chronic host immune responses. In this study, we evaluated the prevalence of serological response to the sexually transmitted bacterium Mycoplasma hominis in patients with rheumatoid arthritis. We show that sera of patients with rheumatoid arthritis are enriched with antibodies specifically recognizing microbial surface antigens compared with the general population. This suggests that M. hominis genital infection, with its peculiar host immunity subversion mechanisms, might play a role in predisposing to the development and progression of chronic arthritis in susceptible individuals. Thus, the range of microbes with a role as triggers of autoimmune disease (P. gingivalis, A. actinomycetemcomitans, Streptococcus spp., and F. nucleatum, among others) might have a new member in M. hominis. The potential role of the interactions taking place at the host–pathogen interface during persistent M. hominis infections in inducing autoimmunity should be further explored and characterized.